"ANALYZING THE IMPACT OF AUTOMOBILE OWNERSHIP ON FINANCIAL WELL-BEING : A COMPARATIVE CASE STUDY OF MALE AND FEMALE AUTO DRIVERS IN THANE CITY". (CAHIERS MAGELLANES-NS, 2024)
In the context of India's escalating population and rapid urbanization, the demand for urban transport has witnessed a pronounced surge. While public transport systems effectively interconnect various parts of cities, they often fall short in reaching interior destinations. Consequently, commuters have increasingly turned to intermediate private transport solutions for their daily commuting needs. Auto drivers emerge as pivotal contributors to urban and semi-urban local transport, serving as complements to public transportation services.Despite their integral role, the plight of auto drivers remains a subject of concern. Many individuals embark on this profession with aspirations of securing a respectable livelihood. Within this profession, auto drivers exhibit diversity in ownership models, with some owning their vehicles and others opting to rent them. This study delves into the nuanced distinctions between male and female auto drivers, specifically focusing on the implications of vehicle ownership on their financial well-being. Through a comprehensive exploration of these dynamics, the research aims to provide insights that contribute to a more informed understanding of the challenges and opportunities faced by auto drivers in the urban and semi-urban transport landscape.